ENGLISH PROFICIENCY AMONG BUSINESS STUDENTS AND ITS IMPACT ON ACADEMIC PERFORMANCE - Saeidah Malik; Mazrah Malek; Saidatunur Fauzi Saidin; Liyana Ahmad Afip , (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Market demand for employees who are proficient in English language has increased nowadays, hence, many developing countries including Malaysia has put high emphasis on their local university graduates' capabilities to master the foreign language by implementing various methods of cultivating the use of English in the university settings. Hence, the main objective of this study is to investigate the impact of English language proficiency on a student’s academic performance in the university. Previous studies conducted in this area simply focuses on either testing the results of language tests or perceptions of students themselves, but none have yet to combine both techniques in investigating the impact, especially in Malaysia. This study utilizes 300 respondents among business students from four (4) public universities in Malaysia. The results of the study suggest that on average the respondents do perceive the importance of being proficient in English in manoeuvring the academic environment in the university. The results also indicate significant effect between students’ secondary results (i.e., SPM) and English entrance exam (i.e., MUET) with students’ academic performance in the university (i.e., CGPA).